Human umbilical cord mesenchymal stem cells recover chemotherapy-induced premature ovarian failure - Ji, Guojie; Wang, Pengbo; Kong, Zhihong; Cao, Xiangxiang; Sun, Zhibin; Yang, Jie; Zhao, Xiaoyang; Feng, Huigen; Hu, Huanhuan (Frontiers in Medicine, 2025)
BackgroundCurrent therapeutic approaches for premature ovarian failure (POF) are often inadequate in clinical practice and some raise ethical concerns. Human umbilical cord mesenchymal stem cells (hUC-MSCs) have emerged as a preferred option for cell transplantation, attributed to their facile extraction process and minimal immunogenicity.Objective and methodsThis study aimed to elucidate the transcriptomic alterations associated with hUC-MSCs treated in the context of POF mice and to explore their underlying biological mechanisms. POF mice were established via injecting cyclophosphamide (CTX) plus busulfan (BU). Subsequently, ovaries and serum were collected after 1 week for model identification. 4 weeks after hUC-MSCs transplantation, ovaries and serum were collected for experimental analysis. Differentially expressed genes (DEGs) were identified using RNA sequencing (RNA-seq), and their expression levels were validated through reverse transcription quantitative polymerase chain reaction (RT-qPCR).ResultsAfter hUC-MSCs therapy, the number of follicles recovered significantly and the atretic follicles decreased significantly. FSH was reduced, AMH and E2 levels were increased in the treatment group, and comparable to the control group. 343 DEGs were detected in the POF group and the treatment group, including 187 up-regulated genes and 156 down-regulated genes. Our comparative analysis of hUC-MSCs treated with POF samples revealed significant involvement of biological pathways and processes related to cell adhesion, proliferation, apoptosis, inflammatory response and immune response.ConclusionOur research offers a novel perspective on the application of hUC-MSCs for the treatment of POF and establishes a foundation for further exploration of their potential clinical applications.